DIDACTIC DESIGN OF MATHEMATICAL REPRESENTATION OF CLASS X VOCATIONAL SCHOOL STUDENTS ON MATRIX MATERIAL - Meika, Ika; Tri Aprilianti, Putri; Ika Yunitasari; Asep Sujana (Universitas Swadaya Gunung Jati., 2023)
Mathematical representation ability (KRM) is one of the basic abilities that must be developed in mathematics learning. One way to develop KRM is by using teaching materials that help reduce students' learning difficulties (learning obstacles). However, in general mathematics learning in schools uses ready-made textbooks without paying attention to learning obstacles (LO). This research aims to identify LO in matrix material in the form of didactical design (teaching materials) for mathematical representations. The method used is Didactical Design Research (DDR) with three stages, namely didactical situation analysis, metapedadidactic analysis, and retrospective analysis. The results of the preliminary study through the LO identification test on matrix material showed that there were obstacles experienced by students regarding KRM, namely understanding the concept of matrices, determining the similarity of matrices, calculation operations on matrices, and real problems in matrix form. Furthermore, the results of the LO identification test showed that 63.6% of students had obstacles, 22.1% of students were in the moderate category and 14.3% of students had no obstacles. To overcome student obstacles in the matrix, a learning design is needed that is developed based on LO analysis to produce a hypothetical didactic design that contains various student activities, predictions of student responses along with their anticipation. The results of the research show that the didactic design provided can anticipate students' LOs towards KRM in the matrix material, indicating that there are no more LOs experienced by students.